2021
DOI: 10.1111/tpj.15546
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis elucidates how shade conditions ameliorate the deleterious effects of greening (Huanglongbing) disease in citrus

Abstract: Summary Under tropical and subtropical environments, citrus leaves are exposed to excess sunlight, inducing photoinhibition. Huanglongbing (HLB, citrus greening), a devastating phloem‐limited disease putatively caused by Candidatus Liberibacter asiaticus, exacerbates this challenge with additional photosynthetic loss and excessive starch accumulation. A combined metabolomics and physiological approach was used to elucidate whether shade alleviates the deleterious effects of HLB in field‐grown citrus trees, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Overall, most of the metabolites in the pathway of carbon fixation in photosynthetic organisms were downregulated, and those distributed in other pathways were upregulated (see Figure 2 and Supplementary Data S3 ). This result is quite consistent with the previous reports [ 19 , 39 45 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Overall, most of the metabolites in the pathway of carbon fixation in photosynthetic organisms were downregulated, and those distributed in other pathways were upregulated (see Figure 2 and Supplementary Data S3 ). This result is quite consistent with the previous reports [ 19 , 39 45 ].…”
Section: Resultssupporting
confidence: 94%
“…Wei et al [ 40 ] also reported that the number of differentially expressed genes (DEGs) related to photosynthesis detected in “Valencia” orange ( C. sinensis ) at one and five days of post- Ca Las-infected psyllid infection was greatly less than that of healthy psyllid infection. Suh et al’s [ 19 ] research indicated the obvious downregulation of metabolites involved in carbon fixation in photosynthetic organisms in the leaves of four-year-old “Hamlin” orange ( C. sinensis ) trees naturally infected by Ca Las before experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not clear if this advantage conferred by IPCs is the result of maintaining trees free from HLB, shading effect, or both combined. Shading can promote tree growth in citrus and improve photosynthesis [14] and may ameliorate HLB symptoms [15]. This possibility merits further evaluation, which is currently being performed in our labs.…”
Section: Discussionmentioning
confidence: 98%
“…In plants, photoassimilates are produced in source tissues (photosynthetically active tissues, such as leaves) and then allowed to be transported to support the growth of sink tissues such as fruits or roots which themselves are unable to produce assimilates or the assimilates produced by themselves are not enough to support their own needs ( Hofius and Börnke, 2007 ; Albacete et al., 2014 ; Suh et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%